INVENTARIS JENIS DAN POTENSI GASTROPODA DI NEGERI SULI DAN NEGERI TIAL - Supusepa, Junita (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2018)
The waters on the Village Suli and Tial have abundant gastropods and are always use as food and decorative materials by the local community. The purpose of this study was to find out species and potential of gastropods in the waters of Village of Suli and Tial. The study uses the line transsect method. The species of gastropods obtained in the waters of Suli Village as many as 611 individuals and Tial as many as 172 induviduals. The waters of Suli Village there are 8 species of gastropod and Tial 16 species of gastropod which can be used for consumption or as raw material for decoration. ABSTRAK Perairan Negeri Suli dan perairan Negeri Tial mempunyai potensi kelimpahan gastropoda dan selalu dugunakan untuk konsumsi dan bahan baku hiasan. Tujuan penelitian adalah mengetahui jenis dan potensi jenis gastropoda di perairan Negeri Suli dan perairan Negeri Tial. Penelitian ini menggunkan metode transek garis. Jenis gastropoda yang ditemukan di perairan Negeri Suli sebanyak 611 individu dan Negeri Tial sebanyak 172 individu. Perairan Negeri Suli ditemukan 8 jenis gastropoda dan perairan Negeri Tial ditemukan 16 jenis gastropoda yang dapat dikonsumsi atau menjadi bahan baku hiasan. Kata Kunci : inventarisasi, Gastropoda, Suli, Tial, potensi